2017
DOI: 10.3892/mco.2017.1385
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring of recurrent and superior laryngeal nerve function using an Airwayscope™ during thyroid surgery

Abstract: Abstract. In thyroid surgery, intraoperative identification and preservation of the recurrent laryngeal nerve (RLN) and superior laryngeal nerve external branch (SLNEB) are crucial. Several reports have proposed that electromyography (EMG) monitoring is an acceptable adjunct for identification and preservation of the RLN. However, a limited number of hospitals have access to an EMG monitoring system. Therefore, the development of another viable monitoring method is required. The aim of the present study was to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…In a study in ten patients, the researchers used a technique called "airway scope" to monitor recurrent laryngeal nerve and SLN intraoperatively. In this study, vocal cord motion, which occurred by stimulation given to recurrent laryngeal nerve and SLN, was visualized by "airway scope" device and it was reported to be an important technique for surgical safety (8). In this study, we observed the polyphasic MUAPs in L-EMG of one patient with vocal cord paralysis.…”
Section: Discussionmentioning
confidence: 80%
“…In a study in ten patients, the researchers used a technique called "airway scope" to monitor recurrent laryngeal nerve and SLN intraoperatively. In this study, vocal cord motion, which occurred by stimulation given to recurrent laryngeal nerve and SLN, was visualized by "airway scope" device and it was reported to be an important technique for surgical safety (8). In this study, we observed the polyphasic MUAPs in L-EMG of one patient with vocal cord paralysis.…”
Section: Discussionmentioning
confidence: 80%